A 5.3 nm giant metal–organic cage and its supramolecular gel for the formation of dye molecular ionic pairs. Issue 15 (23rd March 2023) - Li, Kaixiu; Huang, Jian; Wang, Shi-Cheng; Li, Zhengguang; Wang, Jun; Li, Yiming; Chen, Mingzhao; Chan, Yi-Tsu; Liu, Die; Wang, Pingshan
Abstract : A giant terpyridine-based metal–organic cage with multiple ion pairs and intrinsic cavities was synthesized and the corresponding metal–organic gel displayed good adsorption performance via electrostatic and other non-covalent interactions. Abstract : A terpyridine-based supramolecular cage was successfully synthesized by the self-assembly of a hexapodal metal–organic ligand with Zn 2+ . This metallo-cage exhibited two large parallel planes on the top and bottom with diameters close to 6 nm and a face-to-face distance close to 3.5 nm, thus possessing a large cavity. Electrospray ionization mass spectrometry (ESI-MS), nuclear magnetic resonance (NMR), two-dimensional nuclear Overhauser (2D-NOESY), and diffusion-ordered (DOSY) spectroscopies as well as transmission electron microscopy (TEM) and atomic force microscopy (AFM) measurements, unambiguously supported the formation of a supramolecular cage. Furthermore, the corresponding metal–organic gel was felicitously prepared in CH3 CN/H2 O and displayed good adsorption performance for dye molecules.